Influence of Soot Contamination in API CI-4 Engine Oil on Four-Ball Metallic Wear Using Electron Microscopy Image Analysis - Oungpakornkaew, Pitchaporn; Rungsritanapaisan, Panyakorn; Karin, Preechar; Tongsri, Ruangdaj; Tanprayoon, Dhritti; Hanamura, Katsunori (My University, 2020)
Engine lubricant has an important role in decreasing friction and the wearing of moving parts in the engine. However, soot contaminated in engine oil could change chemical and physical properties that affect the lubricant oil operation. Soot particles were simulated using carbon black in order to eliminate the effect of metallic ash and unburned hydrocarbon, which contained in particulate matter. The carbon black was blended in CI-4 lubricating oil. The investigation of metallic wear was associated with the use of a four-ball wear test. The amount of wear was compared by measuring the wear scar diameter of the worn surface on the steel balls. Scanning electron microscope (SEM) and confocal laser scanning microscopy were used for characterizing wear scar and surface roughness, respectively. In addition, the evidence of lubricant additive elements was detected on the wear surface by Energy Dispersive X-ray analysis (EDX). This research found that engine oil with soot contamination could lead to increasing amounts of abrasive wear by 83% and has approximately 1.1% larger wear scar diameter.